Germinación y desarrollo de la plántula de Cassia grandis L. (Caesalpinioideae) - Flores, Eugenia M.; Rivera, Dora I.; Vásquez, Nelly M. (Revista de Biología Tropical, 1986)
Cassia grandis blooms from January to May and ripe the pods of the precceding year from Frebruary to May. The seeds are hard coated and require mechanical scarification for germination. Germination is epigeal, phancrocotylar and begins 2 to 3 days after sowing seedling development is fast but two months later it becomes very slow. The silvicultural possibilities of the species seem not promising; however, additional studies are required to determine the possible uses of the wood.